DIMENSIONAL ANALYSIS AND EXPERIMENTAL DESIGN FOR PREDICTING THE CALCULATION OF THE VALUE OF THE TORQUE COEFFICIENT ON PROPELLER B-SERIES, CASE STUDY OF B3-50 AND B5-80 - Adietya, Berlian Arswendo; Indiaryanto, Mahendra; S, Sutiyo; Kusuma, Cahya (Journal of Marine-Earth Science and Technology, 2022)
Experimental design is a fairly old method of statistically analyzing an experimental prediction. This is used to replace a fairly old system as well, namely in the form of a trial and error method. Because with this method the response results approach from a study can be predicted statistically. In this study, we will calculate some torque values of a propeller on a displacement ship type. Where the ship's operational displacement ship runs on a Froude number below 0.25, for that the Wageningen B-series propeller type is very suitable for this ship. Furthermore, dimensional analysis is carried out with variables that affect propeller performance and uses multivariate combination calculations. The results of the study show the regression equation between the KQ values of the B-series propeller data and the regression formula with the equation Y = 0.9916x + 0.000835 with the value of R2 being 0.9931. so we try to apply an experimental design method to be validated with the polynomial results of the B-series propeller on blades 3 to 6, so that the statistical method of this experimental design is up-to-date in propulsion design calculations.